Collaboration in achieving sustainable solutions in the textile industry - Abreu, Mônica Cavalcanti Sá de; Ferreira, Fabiana Nogueira Holanda; Proença, João F; Ceglia, Domenico (The Journal of business & industrial marketing, 2021)
Purpose This paper aims to investigate how sustainable solutions in the textiles and clothing industry are decided through business-to-business collaboration. Design/methodology/approach A qualitative and inductive study of the Brazilian textiles and clothing industry is carried out, an industry in which sustainable denim products are increasingly being recognized as subject to competition. The paper adopts a focal net perspective to understand the collaborative arrangements through which firms combine the products they offer as a sustainable solution. Documentary data were collected and in-depth interviews conducted with the top managers of one of the world’s largest denim-manufacturing companies present in the Brazilian market, which is involved in providing sustainable solutions in cooperation with its partners. Findings The authors describe the factors that reflect the conditions for generating a sustainable business performance, including a corporate policy that assumes and articulates the responsibility for social interest, core-business stakeholders and regulatory requirements; a sustainable product-service system (S.PSS) based on innovative interactions between the stakeholders in the value production system; relations between stakeholders that promote business sustainability through a dependable value chain characterized by a sense of collaboration and collective actions; and a business model for sustainability that combines economic with social and ecological value creation. These factors help a business establish a more strategic position in the value network, enabling it to capture more value. Practical implications Sustainable solutions are developed dynamically and collaboratively within an S.PPS. Managers need to focus not only on tangible products but also on intangible services designed and combined so that they are jointly capable of fulfilling customer’s needs and creating social and ecological value. Managers within the solution provider must develop business models for sustainability that are continually evolving to satisfy the interest in resource-efficiency by actors in civil society, business and government. Originality/value The research contributes to the existing literature by applying approaches involving corporate social responsibility (CSR) and strategic nets to the study of the implementation of an S.PSS. Sustainable initiatives and offers developed by an S.PSS are not isolated phenomena but result from collaboration in finding solutions among different actors linked in a strategic net. In this sense, companies need to adjust their business models for sustainability to generate positive economic, social and ecological value and gain credibility for their missions.